A Shift in the Thermoregulatory Curve as a Result of Selection for High Activity-Related Aerobic Metabolism - Stawski, Clare; Koteja, Paweł; Sadowska, Edyta T. (Frontiers in Physiology, 2017)
According to the “aerobic capacity model”, endothermy in birds and mammals evolved as a result of natural selection favouring increased persistent locomotor activity, fuelled by aerobic metabolism. However, this also increased energy expenditure even during rest, with the lowest metabolic rates occurring in the thermoneutral zone (TNZ) and increasing at ambient temperatures (Ta) below and above this range, depicted by the thermoregulatory curve. In our experimental evolution system, four lines of bank voles (Myodes glareolus) have been selected for high swim-induced aerobic metabolism and four unselected lines have been maintained as a control. In addition to a 50% higher rate of oxygen consumption during swimming, the selected lines have also evolved a 7.3% higher mass-adjusted basal metabolic rate. Therefore, we asked whether voles from selected lines would also display a shift in the thermoregulatory curve and an increased body temperature (Tb) during exposure to high Ta. To test these hypotheses we measured the RMR and Tb of selected and control voles at Ta from 10°C to 34°C. As expected, RMR within and around the TNZ was higher in selected lines. Further, the Tb of selected lines within the TNZ was greater than the Tb of control lines, particularly at the maximum measured Ta of 34°C, suggesting that selected voles are more prone to hyperthermia. Interestingly, our results revealed that while the slope of the thermoregulatory curve below the lower critical temperature (LCT) is significantly lower in the selected lines, the LCT (26.1°C) does not differ. Importantly, selected voles also evolved a higher maximum thermogenesis, but thermal conductance did not increase. As a consequence, the minimum tolerated temperature, calculated from an extrapolation of the thermoregulatory curve, is 8.4°C lower in selected ( 28.6°C) than in control lines ( 20.2°C). Thus, selection for high aerobic exercise performance, even though operating under thermally neutral conditions, has resulted in the evolution of increased cold tolerance, which, under natural conditions, could allow voles to inhabit colder environments. Further, the results of the current experiment support the assumptions of the aerobic capacity model of the evolution of endothermy.